2019
DOI: 10.1088/1757-899x/622/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Commercial Grade and Laboratory Grade of TiO2 particle in Nanofluid for Quench Medium in Rapid Quenching Process

Abstract: Heat treatment of material particularly quenching requires a high thermal conductivity quench medium. Hardenability of material, dimension, and geometry of the component are considerate on choosing quench medium. The cooling rate of quenching affects the properties and microstructures by creating specific phase transformation to occur. Enhancing the quench medium by accelerating the cooling rate can be attained by the addition of nanoparticle which has higher thermal conductivity. This nanoparticle-added mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Several types of solid particles can be added to nanofluid, including metals, metal oxides such as CuO, TiO2, and Al2O3, as well as carbon-based particle (Arularasan and Babu, 2021;Ramadhani et al, 2019;Xia et al, 2014). Carbon-based particle, specifically advanced types such as MWCNTs, has garnered increased attention due to the significantly higher thermal conductivity (Chen, Zeng, and Yuan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several types of solid particles can be added to nanofluid, including metals, metal oxides such as CuO, TiO2, and Al2O3, as well as carbon-based particle (Arularasan and Babu, 2021;Ramadhani et al, 2019;Xia et al, 2014). Carbon-based particle, specifically advanced types such as MWCNTs, has garnered increased attention due to the significantly higher thermal conductivity (Chen, Zeng, and Yuan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, solid particles have higher thermal conductivity compared to any fluid. Several particles are commonly added to the fluid, such as metallic particles, metal oxide particles, and even non-metallic particles [5][6][7] . One type of non-metallic particle that is frequently used is carbon-based [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, investigating the reduction in the number of publications between the years 2011 to 2013, the authors have found that during the aforementioned period, researchers have focused essentially on improving the HE designs and the use of renewable sources for providing thermal energy to the system (e.g., solar or biomass). Additionally, the employment of nanofluids has extended beyond that of HEs to applications such as air purification systems [25], quenching media [26][27][28], liquid fuels enhancement [29], medical treatment [30], magnetic sealing [31], nano-lubricants [32,33], and many other usages. This paper will provide an overview of the operating principles of HEs together with a summary of the development of the design of HEs to incorporate the more efficient usage of nanofluids as working media.…”
Section: Introductionmentioning
confidence: 99%